Infrastructure Development And Socio-Economic Disparities In Indonesian Society - Moh Idil Ghufron; Ahmad Ali Bustomi (IJED: International Journal of Economy Development Research, 2022)
Infrastructure development is a good concept for managing the country. In addition, infrastructure development is also an important aspect in increasing economic growth because it can create jobs, reduce poverty and increase per capita income. However, this development also has a significant impact on the socio-economic community. Infrastructure disparities between regions are one of the factors driving economic disparities between regions. Within the territory of Indonesia, this issue is interesting to study and explore, especially since the government is currently prioritizing infrastructure development in various regions in Indonesia.